RELATIONSHIP OF RISK FACTORS FOR STUNTING IN BADUTA AGES 6-24 MONTHS IN BAITUSSALAM DISTRICT ACEH BESAR DISTRICT - Sofia Sofia; Irma Agustina; Nora Sovira; Mulya Safri; Iflan Nouval (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
The problem of stunting in Aceh Besar exceeds the standard set of WHO, which is 38.7% caused by many risk factors. This study aims to determine the risk factors of stunting in children aged 6-24 months in Baitussalam, Aceh Besar. The type of this research is observational analytic with a cross-sectional method that involves 189 children under two years old. Data were collected by filling out questionnaires, maternal and child health books, and measuring body length. The results showed that children who are stunted were 24.3% and those who were not stunted were 75.7%. There were stunting children with a history of non-exclusive breastfeeding (93.5%), pre-term gestational age (82.6%), a history of low birth weight (10.9%), mothers with junior high school education levels (60.9%), fathers with junior high school education level (45.7%) and low family income (68.8%). Statistical test analysis found that the risk factors of stunting have a relationship with history of exclusive breastfeeding (p-value = 0.00), gestational age (p-value = 0.00), history of low birth weight (p-value = 0.022), mother’s education level (p-value = 0.00), father's education level (p-value 0.002) and family income (p-value = 0.00). This study concluded that risk factors which include the history of exclusive breastfeeding, gestational age, history of LBW, education level of mother and father, and family income have a relationship with the incidence of stunting in Baitussalam District, Aceh Besar District.